Analysis Of The Existence Of State Law In Implementing A State Of Emergency In The Covid-19 Situation In Timor-Leste - Lucia de Canossa Silva Hau; Ketut Adi Wirawan (Sociological Jurisprudence Journal, 2023)
Concerning â€œThe Existence of the state of Law in implementing of a State of Emergency in the Covid-19 Situationâ€ is a constitutional reflection. Regarding state issues in the juridical aspect, the researcher sees that there have been multiple lexical interpretations in the use of the words Estado Emergencia and Estado de Esesaun. In the authorâ€™s opinion, this theoretical issue is that the concept of Staatnoodrecht (Netherlands) is divided into two parts, namely Subjective Staatnoodrecht and Objective Staatnoodrecht. There are two formulations of the problem. First, does the real situation of Covid-19, which attacks the population of the entire territory of Timor-Leste, meet the requirements to be declared Timor-Leste in a state of emergency? Second, how is the existence of state law in a state of emergency? This study uses normative juridical methods, including statutory, conceptual, and historical approaches. This research is expected to find basic theoretical ideas to realize the existence of the law state in implementing emergencies in the Covid-19 situation.